THE CONCEPTS OF MASCULINITY IN ADVENTUROUS PROSE FOR YOUNG READERS - Качак, Т. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article throws the light upon basic concepts of masculine discourse in contemporary prose for young readers. It observes that for boys’ text characteristic features are central images of strong, brave, smart boys men and young who perform heroic or adventurous deeds pass through a peculiar initiation, become national heroes; quest of the main hero and the chronotope become a mover of the plot. And construct composition of the text. The author offers a detail analysis of adventurous works by Oleksandr Havrosh and Maria Morozenko and notices that the writers count on traditional concepts of male self-affirmation and represent a normative stereotyped masculine image.